TINDAK TUTUR EKSPRESIF GURU DALAM PEMBELAJARAN BAHASA INDONESIA DI KELAS X MAN 1 SIJUNJUNG - Widya Putri; Tressyalina; Ermawati Arief; Herlin Triana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the forms of teachers’ expressive speech acts and the politeness strategies used in Indonesian language learning at Grade X of MAN 1 Sijunjung. This qualitative study employed a descriptive method, with data collected through the Simak Libat Cakap (SLC) technique. The findings reveal eight forms of expressive speech acts: praising, criticizing, congratulating, blaming, thanking, complaining, insinuating, and apologizing. In addition, four politeness strategies were identified: bald-on-record, positive politeness, negative politeness, and off-record. The findings indicate that the appropriate use of expressive speech acts and politeness strategies supports effective classroom interaction and strengthens teacher–student relationships in the learning process.